Microflora manipulation of artificially reared piglets - Schoenherr, W.D.; Pollmann, D.S.; Kennedy, G.E.; Schoneweis, D.A.; LaForge, R.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three experiments were conducted with pigs to examine the influence of two antimicrobial agents on growth, blood parameters, the intestinal flora population and the therapeutic action on mycoplasma pneumonia. The pigs were fed a medicated milk replacer for 21 days in individual cages in an environmentally controlled room. In Experiment 1, pigs received two levels of lincomycin (L): 5 mg (LILO) and 10 mg (LIHI) injection per pound of body weight, and two levels of long-acting oxytetracycline (LAO): 100 mg (LALO) and 200 mg (LAHI) per injection and were compared to a control. Growth, feed efficiency, scour score, severity of mycoplasma pneumonia, leukocyte and erythrocyte counts were evaluated. LAHI reduced growth, feed efficiency and blood parameters. The LIHI pigs had a slight improvement in growth, feed efficiency and leukocyte count over the LILO pigs. These data suggest that the correct dosage rate of LAO is 100 mg per injection and of L is 10 mg per pound of body weight for improvement in performance of artificially reared piglets. In Experiment 2, coliform (EC) and lactobacillus (LB) counts from five portions of the gastrointestinal tract plus the feces were enumerated. The LAO increased EC and LB in the stomach. A combination treatment of LAO+L decreased LB in the stomach and depressed EC in the colon. Forty additional piglets were allotted to a nursery study to determine the effect of isolation after antimicrobial therapy on growth parameters and mycoplasma pneumonia. Isolation had no effect on growth or mycoplasma pneumonia during the nursery phase. In Experiment 3, piglets were challenged with mycoplasma pneumonia after antimicrobial therapy. No differences were observed in any portion of the lung for severity of mycoplasma pneumonia. The culture of mycoplasma pneumonia either did not infect the piglets or they showed no evidence of it's presence.
Keywords: Swine; Microflora manipulation; Artificially reared piglets